The Effect of Nitrogen Enrichment on C1-Cycling Microorganisms and Methane Flux in Salt Marsh Sediments - Irvine, Irina C.; Vivanco, Lucía; Bentley, Peris N.; Martiny, Jennifer B. (Frontiers in Microbiology, 2012)
Methane (CH4) flux from ecosystems is driven by C1-cycling microorganisms – the methanogens and the methylotrophs. Little is understood about what regulates these communities, complicating predictions about how global change drivers such as nitrogen enrichment will affect methane cycling. Using a nitrogen addition gradient experiment in three Southern California salt marshes, we show that sediment CH4 flux increased linearly with increasing nitrogen addition (1.23 µg CH4 m-2 d-1 for each g N m-2 yr-1 applied) after seven months of fertilization. To test the reason behind this increased CH4 flux, we conducted a microcosm experiment altering both nitrogen and carbon availability under aerobic and anaerobic conditions. Methanogenesis appeared to be both nitrogen and carbon (acetate) limited. N and C each increased methanogenesis by 18%, and together by 44%. In contrast, methanotrophy was stimulated by carbon (methane) addition (830%), but was unchanged by nitrogen addition. Sequence analysis of the sediment methylotroph community with the methanol dehydrogenase gene (mxaF) revealed three distinct clades that fall outside of known lineages. However, in agreement with the microcosm results, methylotroph abundance (assayed by qPCR) and composition (assayed by T-RFLP) did not vary across the experimental nitrogen gradient in the field. Together, these results suggest that nitrogen enrichment to salt marsh sediments increases methane flux by stimulating the methanogen community.